Uji Aktivitas Antioksidan Buah dan Sirup Markisa Ungu Menggunakan Metode DPPH - Slamet Hadi Kusumah; Suci Apsari Pebrianti; Laila Maryatilah (Jurnal Fakultas Teknik Kuningan, 2021)
purple passion fruit contains several bioactive compounds such as carotenoid, anthocyanin, flavonoid, and vitamin C which can act as antioxidant. Being one of those sources of natural antioxidant, consumption of passion fruit and its processed products can help to inhibit or delay the cellular damage caused by free radicals. This research aims to determine the antioxidant activity in raw purple passion fruit and its syrup by using DPPH method at 517 nm and expressed as IC50 value. The results showed that purple passion fruit had very strong antioxidant activity with IC50 values ​​of 9.76 ppm and 45.78 ppm, respectively. The lower antioxidant activity of purple passion fruit syrup was presumably affected by the treatment during syrup production. The heating process can lead to breakage of antioxidant compounds, resulting in decreased antioxidant activity of purple passion fruit syrup. Our research show that purple passion fruit and its syrup have an antioxidant activity so it can be used and consumed as source of natural antioxidant.